The C-reactive protein to albumin ratio predicts postoperative complication in patients who undergo gastrectomy for gastric cancer. Issue 6 (June 2020) - Lee, Jin Won; Sharma, Ashish Ranjan; Lee, Sang-Soo; Chun, Wan Joo; Kim, Hae Sung
Abstract: The aim of this study was to evaluate the preoperative C-reactive protein (CRP) to albumin ratio (CAR) of patients with gastric cancer and to investigate the factors correlated with perioperative complications. From March 2016 to December 2019, 128 patients who underwent curative gastrectomy for gastric cancer were enrolled in a retrospective study. The preoperative cutoff value of the CAR for predicting postoperative complications was 0.265 on receiver operating characteristic (ROC) curve analysis. Clinical characteristics were compared between patients with complications (Clavien-Dindo grade ≥2, n = 20) and without complications (Clavien-Dindo grade <2, n = 108). On univariate and multivariate analyses, estimated blood loss (EBL) during the operation (HR 1.003, p = 0.039) and CAR (HR 2.832, p = 0.045) were independent predictors of postoperative complications. In conclusion, preoperative CAR appears to be a predictor of postoperative complications in the patients undergoing surgical treatment of gastric cancer. Abstract : Gastrointestinal system; Pathology; Surgery; Immunology; Oncology; Clinical research; C-reactive protein to albumin ratio, Gastric cancer, Postoperative complication.